Proceedings of the 6th International Conference on Educational, Management, Administration and Leadership 2016
DOI: 10.2991/icemal-16.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Women Athletes Endurance and Menstruation Cycle; Pre-Menstruation, 2nd day of Menstruation and 5th Day of Menstruation

Abstract: Raised the issue about menstruation effects towards athlete's endurance, formally as a research, can help athletes and coach to anticipate any matter that can affect athlete's activity. The aim of this research is to know the difference of menstruation cycle towards women athletes' endurance in several sports number. This research was using the descriptive method, with three shoot case design. Subjects in this research were soccer women athletes in UPI student unit activity and Rowing Women Athletes in Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Six studies [ 53 , 88 , 91 , 92 , 104 , 109 ] demonstrated MC phase differences in aerobic exercise performance or applied physiological outcomes related to aerobic performance; two studies found some outcomes were affected by MC phase while others were unaffected [ 52 , 90 ], and the majority of studies ( n = 14) concluded MC phase had no affect [ 46 , 52 , 54 , 86 , 87 , 93 , 96 , 97 , 98 , 105 , 107 , 108 , 110 , 111 ]. Continuous endurance performance measured with time to exhaustion tests [ 52 , 87 , 90 ], power output during maximal treadmill [ 86 ] and cycle [ 97 , 105 ] and rowing [ 111 ] tests and a 2000 m rowing time trial [ 93 ] was not affected by MC phase.…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies [ 53 , 88 , 91 , 92 , 104 , 109 ] demonstrated MC phase differences in aerobic exercise performance or applied physiological outcomes related to aerobic performance; two studies found some outcomes were affected by MC phase while others were unaffected [ 52 , 90 ], and the majority of studies ( n = 14) concluded MC phase had no affect [ 46 , 52 , 54 , 86 , 87 , 93 , 96 , 97 , 98 , 105 , 107 , 108 , 110 , 111 ]. Continuous endurance performance measured with time to exhaustion tests [ 52 , 87 , 90 ], power output during maximal treadmill [ 86 ] and cycle [ 97 , 105 ] and rowing [ 111 ] tests and a 2000 m rowing time trial [ 93 ] was not affected by MC phase.…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
“…The trivial effect of MC phase on performance observed in previous systematic reviews [5,67] is understandable as the findings from this narrative review are mixed, with 20 of the 35 relevant studies concluding that MC did not produce significant improvements or impairments to physical performance, and 15 studies finding that at least one outcome was affected by MC phase. Seven of the twenty-four studies that measured performance in the early follicular and late luteal phases, when performance was perceived to be diminished [75,76], demonstrated a performance reduction in the early follicular [21,68,103,104] or late luteal phases [68,91,101,104,109] compared to other MC phases. Figure 2 demonstrates that more performance outcomes were relatively reduced in the late luteal phase than any other MC phase.…”
Section: Overall Impact Of Menstrual Cycle Phase On Physical Performancementioning
confidence: 99%
“…However, this daily fluctuation in performance can be altered by several factors such as the type and intensity of exercise, age, nutritional status, training schedule, level of physical activity, and sleep deprivation ( Saidi et al, 2021 ; Mejri et al, 2015 ; Souissi et al, 2020 ). Additionally, the variations in hormonal climate that accompany the different menstrual cycles in women could certainly affect the characteristics of diurnal fluctuations in sports performance ( Mejri et al, 2015 ; Souissi et al, 2020 ; Carmichael et al, 2021 ; Julian et al, 2017 ; Romero-Moraleda et al, 2017 ; Giacomoni et al, 2000 ; Sutresna, 2016 ).…”
Section: Introductionmentioning
confidence: 99%